Development of freezing process of phase change materials in cylindrical thermal energy storage tanks with various fin configurations - Seyyed Amirreza Abdollahi; Saman Faramarzi; Behnam Azizi Gheshlaghchaei; Sana Sahaf Amin; Mohammad Hossein Heidarshenas; Hamid Majidi; Faramarz Talati (Scientific Reports)
Abstract One of the most effective methods for thermal energy storage relies on the latent heat property of phase change materials (PCMs). Fins are widely employed as an efficient technique to enhance heat transfer. However, precise modeling of the freezing process remains challenging due to the dynamic nature of the phase change boundary. This study introduces a novel semi-analytical approach based on Green’s function to investigate the impact of radial and longitudinal fins on the freezing process within cylindrical thermal energy storage tanks under time-dependent first and third type boundary conditions. Unlike previous studies that primarily focused on steady-state conditions or simplified geometries, this research provides a more realistic and comprehensive analysis of transient thermal behavior. The findings reveal that while fins initially accelerate freezing, their effectiveness diminishes over time due to thermal resistance effects. Radial fins consistently outperform longitudinal fins, reducing total freezing time by up to 75.31% and demonstrating a 19.68% efficiency improvement. These results offer new insights for optimizing the design of thermal energy storage systems, particularly in applications requiring efficient cold energy storage under varying boundary conditions.